Avaliação dos efeitos induzidos pelo envenenamento da peçonha de Bothrops mattogrossensis (jararaca-pintada) sobre as alterações do sistema purinérgico e a potencial inibitório do especiosídeo extraído da Tabebuia aurea (Ipê amarelo) - DHÉBORA ALBUQUERQUE DIAS (2024)
It is estimated that 5.4 million people worldwide are bitten by snakes. Every year, 100,000 people die and 300,000 people need amputations or develop other permanent disabilities as a result of snake bites. Snakebite accidents are considered a serious problem in isolated locations in Brazil and are generally attributed to snakes of the genera Bothrops, Crotalus and Lachesis. Snake venom contains various proteolytic toxins that promote local and systemic poisoning symptoms, including cell death and proteolytic activity, neurotoxicity, inflammation, coagulation and haemorrhagic effects. At the site of the bite, the injury promotes cell lysis and the release of intracellular content, with an increase in extracellular levels of nucleotides such as ATP and its derivatives that act as chemotactic molecules, leading to the activation of the inflammatory process and cell differentiation, potentiating the response to venom toxins. Snake venom can release ectoenzymes and nucleotidases that modulate the purinergic system. In addition, the modulation of ectoenzymes of the purinergic system, such as ectonucleoside triphosphate diphosphohydrolase, ecto-5'-nucleotidase and adenosine deaminase, are involved in snake envenomation. Serotherapy is the treatment of choice for snake poisoning, but it does not neutralise local reactions, which can lead to serious sequelae, such as partial or total loss of the affected area. This study aimed was of this study was to verify the presence and activity of nucleotidases in the crude venom of Bothrops mattogrossensis (BmtV) in vitro and to characterize the modulation of purinergic components, myeloid differentiation and markers of inflammatory/oxidative stress by BmtV in vivo and in vitro. In addition, our study evaluated the inhibitory activities of specioside, an iridoid isolated from Tabebuia aurea, against the effects of BmtV. Proteomic analysis of venom content and nucleotidase activity confirms the presence of enzymes similar to ectonucleotidase in BmtV. In in vivo experiments, BmtV altered the expression of purinergic components (P2X7 receptor, CD39 and CD73), increased the number of neutrophils in peripheral blood and elevated oxidative stress/inflammatory parameters such as lipid peroxidation and myeloperoxidase activity. Specioside was able to inhibit nucleotidase activity, restore neutrophil numbers and mediate the oxidative/inflammatory effects produced by BmtV. We highlight the effects produced by BmtV on the components of the purinergic system, on myeloid differentiation and on inflammatory/oxidative stress parameters, while the use of specioside reduced the main BmtV-dependent effects. These results showed the involvement of the purinergic system in BmtV poisoning and corroborated the efficacy of specioside, a molecule found in the bark and seeds of Tabebuia aurea, which is used empirically against inflammation caused by ophidian poisoning.